2011
DOI: 10.1128/iai.05631-11
|View full text |Cite
|
Sign up to set email alerts
|

Filifactor alocis Has Virulence Attributes That Can Enhance Its Persistence under Oxidative Stress Conditions and Mediate Invasion of Epithelial Cells by Porphyromonas gingivalis

Abstract: Filifactor alocis, a Gram-positive anaerobic rod, is one of the most abundant bacteria identified in the periodontal pockets of periodontitis patients. There is a gap in our understanding of its pathogenicity and ability to interact with other periodontal pathogens. To evaluate the virulence potential of F. alocis and its ability to interact with Porphyromonas gingivalis W83, several clinical isolates of F. alocis were characterized. F. alocis showed nongingipain protease and sialidase activities. In silico an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
173
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(187 citation statements)
references
References 65 publications
12
173
0
2
Order By: Relevance
“…Filifactor alocis is a fastidious, Gram-positive anaerobic rod found to be highly prevalent and abundant in patients with generalized aggressive periodontitis and chronic periodontitis (49). This organism encodes several virulence factors, which may play a role in the pathogenesis of periodontal disease by enabling the organism to persist in periodontal pockets (50). Members of the phylum Synergistetes, a newly recognized phylum of Gram-negative anaerobic bacteria, were recently implicated in periodontal disease (51).…”
Section: Discussionmentioning
confidence: 99%
“…Filifactor alocis is a fastidious, Gram-positive anaerobic rod found to be highly prevalent and abundant in patients with generalized aggressive periodontitis and chronic periodontitis (49). This organism encodes several virulence factors, which may play a role in the pathogenesis of periodontal disease by enabling the organism to persist in periodontal pockets (50). Members of the phylum Synergistetes, a newly recognized phylum of Gram-negative anaerobic bacteria, were recently implicated in periodontal disease (51).…”
Section: Discussionmentioning
confidence: 99%
“…Research is warranted on this type of microorganisms as they may play an important role in development of periodontitis. As a matter of fact, Filifactor alocis, a fastidious, Grampositive, obligate anaerobic rod, has been proven to harbor characteristics in common with established periodontal pathogens and has the potential to contribute to periodontal tissue destruction (Aruni et al, 2011;Moffatt et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of bacterial species detected in subgingival plaque from subjects affected by periodontitis have consistently revealed the presence of bacteria such as Treponema denticola, Porphyromonas gingivalis, Tannerella forsythia, Fusobacterium nucleatum, Prevotella intermedia and Parvimonas micra (Ali et al, 1994;Socransky et al, 1998;Mayanagi et al, 2004). More recent studies have indicated that bacteria such as Filifactor alocis (Aruni et al, 2011;Moffatt et al, 2011) may also be associated with the development of periodontal disease. In vitro models of infection suggest that synergistic interactions between these periodontal bacteria can be related to severity of disease (Kesavalu et al, 2007;Bakthavatchalu et al, 2011;Orth et al, 2011).…”
Section: Introductionmentioning
confidence: 99%